Diagnosis and Treatment Approaches in Infantile Colic (IC): Results of a Survey Among Paediatricians in Turkey - Samil Hizli; Demet Can; Ilknur Kiliç; Emel Örün; Turan Tunç; Hasan Özkan (Frontiers Media S.A., 2021)
Background and Objective: Due to limited knowledge on the etiopathogenesis of infantile colic (IC) and the insufficiency of data regarding current treatments, different approaches emerge in terms of diagnosis, and treatment modalities globally and also in Turkey. The objective of this study was to observe how infantile colic is diagnosed and treated by paediatricians in Turkey.Methods: An anonymous electronic questionnaire was used to collect the respondents' opinions. The study questionnaire was comprised of 4 different sections with 56 multiple-choice questions covering demographic features, diagnostic approach, treatment preferences and response to treatment.Results: A total of 375 paediatricians responded to the survey. Fifty three percent of the participants stated that they established the IC diagnosis based only on their clinical experience. Factors that most affected the decision to start treatment were identified as parent discomfort, decreased family quality of life, and crying duration (68, 66, and 54%, respectively). Application of soothing methods, probiotics, and simethicone were identified as the most frequently used treatment modalities (frequency ranking; 81, 76, and 50%, respectively). Of the participants, 98% stated that they used probiotic as supplements, on the other hand, 72% of the participants indicated that they used simethicone as the only medical treatment to treat IC. The question about the participants' observations regarding the response to probiotic treatment was answered by 71% of the participants with decreased crying duration, while easier stool/gas passage and resolved digestion problems were the other frequent observations (54 and 49%, respectively). The observations related to the response to simethicone treatment also included decreased crying duration in addition to decreased crying periods after feeding and easier gas/stool passage (67, 47, and 44%, respectively).Conclusions: Survey results revealed that the majority of the paediatricians used their clinical experience alone to establish the diagnosis of IC and preferred probiotic supplements and simethicone as the only medical treatment to treat IC and they observed clinical benefits from them. Insights generated by this study will be helpful to guide future efforts to improve the management of infantile colic by paediatricians.